Biogenic amines and the importance of starter cultures for malolactic fermentation. (5th October 2020) - Emer, C.D.; Marques, S.; Colla, L.M.; Reinehr, C.O.
Abstract: Biogenic amines are compounds produced mainly by microorganisms from the decarboxylation of some amino acids which may cause several health issues in susceptible people. In the winemaking process, one of the factors with the greatest impact on the final concentration of biogenic amines in wine is the malolactic fermentation, which mainly involves the action of lactic acid bacteria. This article gathers scientific literature on the importance of the use of inoculation in winemaking, especially for the potential formation of biogenic amines in spontaneous fermentations, with emphasis on malolactic fermentation. It establishes the set of attributes that influence the formation of biogenic amines in winemaking and aspects related to their toxicity, especially histamine and tyramine. With the growing interest of the market in products with less chemical appeal, the safety of wines, whether from non‐conventional or traditional winemaking, must increasingly be observed. Therefore, the importance of using cultivated starter cultures is discussed, along with the safety of organic wines and the presentation of articles that seek to reconcile the production of organic wine with the preservation of the 'microbiological terroir' in a safe way, using selected wild yeasts and lactic acid bacteria.